The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11062-010-9100-5
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Significance of the Stimulus and Features of the Personality as Factors Reflected in the Pattern of Evoked EEG Potentials

Abstract: This review generalizes the data of modern studies of individual peculiarities of the spatial/temporal and amplitude characteristics of evoked EEG potentials (EPs) in humans. A brief description of EPs, characteristics of their components, sources of generation, and functional correlates is presented. Possible effects of the emotional significance of the stimulus and of individual peculiarities of the personality on the amplitude/temporal characteristics of EPs are considered. It is supposed that the aminergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 185 publications
1
2
0
Order By: Relevance
“…The N170 component of visual ERPs is a negative waveform peaking approximately 155-190 msec post-stimulus. It is mostly observed in the occipito-temporal sites and, as is commonly supposed, represents the earliest stage of facial structure encoding [17,19]. Our detection method for this component was in line with earlier experiments.…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…The N170 component of visual ERPs is a negative waveform peaking approximately 155-190 msec post-stimulus. It is mostly observed in the occipito-temporal sites and, as is commonly supposed, represents the earliest stage of facial structure encoding [17,19]. Our detection method for this component was in line with earlier experiments.…”
Section: Methodssupporting
confidence: 85%
“…Among the variety of methods used in face recognition studies, recording of event-related potentials (ERPs) is one of the most well-established techniques currently applied to investigate the time course of neural responses to different facial expressions. The key component in the face and facial expression studies using ERPs is the N170 deflection [17,18]. Recent studies demonstrated that patients with schizophrenia exhibit reduced N170 amplitudes during neutral and emotional face processing [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…At present, a significant increase in the number of studies dealing with the neurophysiological basis of emotional reactions in humans is observed (the respective information is presented in a few reviews [1,2]). According to modern psychological and physiological theories emphasizing the differentiated structure of emotional reactions [3], the first stage of development of such responses is based on perception of emotiogenic information, including decoding of external (auditory, visual, tactile, etc.)…”
Section: Introductionmentioning
confidence: 99%